Faktor Penentu Profitabilitas Pada Perusahaan Manufaktur Sektor Consumer Goods - Olsha Fisena; Indra Widjaja (Jurnal Manajerial Dan Kewirausahaan, 2020)
The purpose of this study is to examine the effect of debt to total assets ratio, current ratio, efficiency, and corporate growth on profitability on manufacturing companies in the sector of consumer goods listed in Indonesia Stock Exchange in the period 2015-2018. Number of samples are 36 samples by purposive sampling method. Data were collected through Indonesia Stock Exchange official website, which are idx.co.id and idnfinancials.com. Data were processed by using Eviews10 software. The results in this study show that debt to total assets ratio has a positive significant effect on profitability (ROE). Efficiency (TATO) has a negative significant effect on profitability (ROE). While current ratio and corporate growth (asset growth) have no significant effect on profitability (ROE). The purpose of this study is to examine the effect of debt to total assets ratio, current ratio, efficiency, and corporate growth on profitability on manufacturing companies in the sector of consumer goods listed in Indonesia Stock Exchange in the period 2015-2018. Number of samples are 36 samples by purposive sampling method. Data were collected through Indonesia Stock Exchange official website, which are idx.co.id and idnfinancials.com. Data were processed by using Eviews10 software. The results in this study show that debt to total assets ratio has a positive significant effect on profitability (ROE). Efficiency (TATO) has a negative significant effect on profitability (ROE). While current ratio and corporate growth (asset growth) have no significant effect on profitability (ROE).